Lang Building - Kjysten Drew:::Creator::::::::::::
Lang Building. 31 West Market Street, Salinas, California. In East of Eden, 'There was always some little delicacy, very special and good--...pastry bought at Lang's Bakery, just across Main Street' (p.324). Original is slide.